Rządzenie publiczne - misja czy profesjonalizacja - Wojciechowski, Eugeniusz (Public Governance - Mission or Professionalism?, 2006)
The content of paper are comments and remarks regarding chosen parts of the public management process. It has complex and multiple character. As a whole the article underlines some problems and provokes to take up the discussion on this topic. The issue of started deliberation is to reply to the question considering proportion between public service (mission) and professional management (professionalism) in the process of public governance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 641-649